Association between oral health status and future dietary intake and diet quality in older men: The PRIME study. (January 2020) - Logan, D.; McEvoy, C.T.; McKenna, G.; Kee, F.; Linden, G.; Woodside, J.V.
Abstract: Objectives: This study investigated whether oral health status, defined as number of natural teeth and subsequent prosthodontic rehabilitation, was associated with future dietary intake and diet quality in older adults in The Prospective Epidemiological Study of Myocardial Infarction (PRIME). Methods: PRIME was originally established to explore cardiovascular risk factors in 50−59 year old men in Northern Ireland (1991–1994). A rescreening phase assessed oral health (2001–2004), while diet was assessed in 2015. Diet quality was characterised by the Dietary Diversity Score and Mediterranean Diet Score. In the current analysis, associations between oral health status, dietary intake and quality were assessed using regression models in 1096 participants. Results: Amongst study participants, the overall mean number of teeth was 18.5, 51.5 % had ≥21 natural teeth and 49.6 % wore dentures. Oral health status was categorised into five groups: 21–28 teeth with (n = 111) and without (n = 453) dentures, 1–20 teeth with (n = 354) and without (n = 99) dentures and edentate with dentures (n = 79). After full adjustment, men with ≥21 teeth and dentures had a higher future intake of fruit, vegetables, and nuts, and diet quality scores, compared to those with <21 teeth with dentures. Edentate men with dentures were less likely to achieve the future fruit dietary recommendation. Conclusions: Having ≥21 natural remaining teeth positively affected the future intake of fruit, vegetables, and nuts, as well as diet quality. Dentures may be beneficial in men with ≥21 natural remaining teeth, as they were associated with an increased future intake of fruit, vegetables, and nuts and better diet quality. Clinical significance: Oral health status is associated with dietary intake, after an average time period of 13 years, with those with a larger number of natural teeth having a better diet quality. Further research is required to investigate this relationship in larger, diverse populations with more detailed dietary assessment.